The Impact of Scientific Knowledge Questions Using Google Forms in conducting review sessions in Biology - Franco , Adona A.; Galano , Jasmin; Luna, Mikee; Ayohan, Joshua; Manansala , France Ace (International Journal of Psychosocial Rehabilitation, 2020)
–This study aimed to know the effectiveness of scientific knowledge questions using Google form in conducting review sessions in Biology.It sought to answer the problems with regard to the performance of the students in the pretest and posttest in the four competencies namely: description of how the nervous system coordinates and regulates these feedback mechanisms to maintain homeostasis; explanation of how protein is made using information from DNA; explanation of how mutations may cause changes in the structure and function of a protein and explanation of how fossil records, comparative anatomy and genetic information provide evidence for evolution.The study utilized the Pretest and Posttest Design and underwent pilot testing and expert validation of master teachers and a Science Coordinator. The control and experimental groups were identified using fish bowl technique. Thirty five (35) students were used in both experimental and control groups. Pretest was given to both groups. Respondents from the experimental group were asked to answer scientific knowledge questions using Google form during review sessions for five (5) weeks. On the other hand, the respondents from the control group were given conventional way of conducting a review. After five (5) weeks, posttest was given to both groups. The pretest and posttest results were gathered and analysed through appropriate statistical treatment using SPSS Volume 21. The respondents in the experimental group were also interviewed to get their perceptions in answering scientific knowledge questions.who answered scientific knowledge questions using Google form during review sessions in Biology with a mean difference of 10.94.There was a significant difference between the pretest and post test mean scores of both experimental and control groups. Furthermore, most of the students in the experimental group said that answering scientific knowledge question using Google form helps them analyze the questions, enables them to understand the lessons well and helps them recall the lessons they’ve learned.It suggests that answering scientific knowledge questions using Google form in review sessions in Biology develops student’s analysis and deeper understanding about the concepts being taught. It can be concluded that better result is achieved since students are more engaged because videos and pictures are included in Google form. Google form is an effective tool in developing students’ skill in answering and analysing higher order thinking skills questions.